PEMBELAJARAN DARING KOTOBA (KOSAKATA) BAHASA JEPANG DI SMAN 8 PEKANBARU - Febri Nur Dwiyanti; Nela Naila Nidhafar; Luthfi Fadhillah Anshar; Reni Erita; Dini Budiani (JURNAL MANAJEMEN PENDIDIKAN, 2022)
Vocabulary is an important element in mastering a language. Because having a good quantity and quality of vocabulary affects the use of good language too. In learning vocabulary, learning strategies are needed. However, vocabulary learning that usually done in class (offline) has turned into online learning (online) due to the COVID-19 Pandemic. This study aims to describe (1) the vocabulary online learning strategies used by Japanese language teachers at SMAN 8 Pekanbaru, (2) the obstacles experienced by teachers in teaching Japanese vocabulary online at SMAN 8 Pekanbaru. The subjects of this study were Japanese language teachers at SMAN 8 Pekanbaru. The data were collected by means of observation, interviews, and documentation, then analyzed using descriptive qualitative methods. The results showed that (1) the learning strategies used in online learning of Japanese vocabulary at SMAN 8 Pekanbaru were drill, question and answer, lecture and assignment giving strategies; (2) The obstacles faced by the Japanese language teacher at SMAN 8 Pekanbaru were weak internet networks that made it difficult for teachers to teach and students had difficulty understanding the vocabulary material being taught, students who did not activate the camera made it more difficult for the teacher to monitor students while learning.